1995
DOI: 10.1111/j.1365-2958.1995.tb02350.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Zymomonas mobilis glucose facilitator gene product (glf) in recombinant Escherichia coli: examination of transport mechanism, kinetics and the role of glucokinase in glucose transport

Abstract: Zymomonas mobilis is known to transport glucose by a facilitated diffusion process. A putative glucose facilitator gene (glf), closely related to a large family of glucose transporters, is located in a cluster of genes that code for enzymes of glucose metabolism. The Z. mobilis glf gene is able to complement glucose transport in an Escherichia coli strain that is defective in native glucose transport and glucokinase. In this study, the recombinant E. coli was shown to be capable of influx counterflow when prel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
86
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(91 citation statements)
references
References 32 publications
1
86
1
Order By: Relevance
“…We found that the use of ice-cold dilution-and-wash buffer, containing an excess of unlabeled TOC, was sufficient to give us reproducible results. The presence of unlabeled TOC was apparently crucial in lowering the binding of TOC to the filters, and the use of a wash solution cooled to subzero temperature (20) was not necessary in our system. The time course of accumulation of TOC by everted membrane vesicles of CS1253, measured by this method, showed that the accumulation process was nearly linear with time during the first 30 s and essentially reached the steady state in about 1 min (Fig.…”
Section: Vol 179 1997 Active Efflux Of Bile Salts By E Coli 2513mentioning
confidence: 99%
See 2 more Smart Citations
“…We found that the use of ice-cold dilution-and-wash buffer, containing an excess of unlabeled TOC, was sufficient to give us reproducible results. The presence of unlabeled TOC was apparently crucial in lowering the binding of TOC to the filters, and the use of a wash solution cooled to subzero temperature (20) was not necessary in our system. The time course of accumulation of TOC by everted membrane vesicles of CS1253, measured by this method, showed that the accumulation process was nearly linear with time during the first 30 s and essentially reached the steady state in about 1 min (Fig.…”
Section: Vol 179 1997 Active Efflux Of Bile Salts By E Coli 2513mentioning
confidence: 99%
“…However, it did not allow us to measure the initial rates of uptake. For this purpose, we developed a modified filtration method, based on the rapid quench filtration method described for the measurement of facilitated glucose transport in Zymomonas mobilis (20). We found that the use of ice-cold dilution-and-wash buffer, containing an excess of unlabeled TOC, was sufficient to give us reproducible results.…”
Section: Vol 179 1997 Active Efflux Of Bile Salts By E Coli 2513mentioning
confidence: 99%
See 1 more Smart Citation
“…Semiquantitative measurement of gluconate transport was conducted as described by Istúriz et al (15). The method for kinetic measurements of GntP-mediated gluconate transport was a slight modification of the procedure of Walsh et al (31), as described previously (23). For determination of the substrate specificity of GntP, uptake of 50 M radioactive gluconate was assayed in the presence of a fourfold excess of unlabelled sugars.…”
mentioning
confidence: 99%
“…For determination of the substrate specificity of GntP, uptake of 50 M radioactive gluconate was assayed in the presence of a fourfold excess of unlabelled sugars. The assay was conducted as described previously (23). The data were analyzed by using Enzfitter software (Biosoft, Cambridge, United Kingdom).…”
mentioning
confidence: 99%